2018
DOI: 10.3390/ijms19092774
|View full text |Cite
|
Sign up to set email alerts
|

Spatholobus suberectus Ameliorates Diabetes-Induced Renal Damage by Suppressing Advanced Glycation End Products in db/db Mice

Abstract: Spatholobus suberectus (SS) is a medicinal herb commonly used in Asia to treat anemia, menoxenia and rheumatism. However, its effect of diabetes-induced renal damage and mechanisms of action against advanced glycation end-products (AGEs) are unclear. In this study, we evaluated the effects of SS on diabetes-induced renal damage and explored the possible underlying mechanisms using db/db type 2 diabetes mice. db/db mice were administered SS extract (50 mg/kg) orally for 6 weeks. SS-treated group did not change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…These natural compounds showed antioxidant effects and exerted anti-diabetic and anti-lipogenic potentials in in vitro studies [21][22][23][24][25]. In the current study, a high dose of LBE supplementation reduced the levels of HbA1c along with RAGE, which was considered as an index of chronic hyperglycemic states [26], although a low dose of LBE treatment decreased only HbA1c, which is a more useful clinical biomarker of diabetes. Therefore, one can conclude that LBE is beneficial for attenuating the hyperglycemic condition in T2DM.…”
Section: Discussionmentioning
confidence: 53%
“…These natural compounds showed antioxidant effects and exerted anti-diabetic and anti-lipogenic potentials in in vitro studies [21][22][23][24][25]. In the current study, a high dose of LBE supplementation reduced the levels of HbA1c along with RAGE, which was considered as an index of chronic hyperglycemic states [26], although a low dose of LBE treatment decreased only HbA1c, which is a more useful clinical biomarker of diabetes. Therefore, one can conclude that LBE is beneficial for attenuating the hyperglycemic condition in T2DM.…”
Section: Discussionmentioning
confidence: 53%
“…And blood stasis, as discussed above, is considered by TCM a significant pathogenetic mechanism of pDPN. Recently, it demonstrated that the extracts of Spatholobi Caulis have neuroprotective effects and inhibit the effects of diabetes-induced glucotoxicity for its improvement in apoptotic phenotypes and oxidative stress [41,42]. Paeoniae Radix Alba is known for its analgesic activity and has been widely used to treat pain-related diseases with Glycyrrhizae Radix; it has been recently explored that the combination of two herbs possesses an obvious analgesic and antiinflammatory effect and the potential molecular mechanism might be due to the increasing expression and function of transient receptor potential ion channel protein vanilloid receptor 1 (TRPV1) channel [43].…”
Section: Discussionmentioning
confidence: 99%
“…The AGE cross-link breaking and inhibition assay was performed according to a method described previously [30]. For the AGEscollagen cross-link breaking analysis, 1 mg/mL of peroxidase labeled MG-BSA was pre-incubated in collagen-coated 96-well plates at 37°C for 4 h. Thereafter 1 mM of ALT-711 or S. aromaticum (50, 100, and 200 µg/mL) was added and incubation was done for 24 h. To confirm the inhibitory activity of S. aromaticum extract on AGEs-collagen cross-link formation, 1 mg/mL of peroxidase-labeled MG-BSA was incubated in the presence or absence of AG or S. aromaticum (50, 100, and 200 µg/mL) in collagen-coated 96-well plates at 37°C for 24 h. The cross-link breaking and inhibitory activities of S. aromaticum were detected using tetramethylbenzidine substrate on a microplate reader at a wavelength 450 nm.…”
Section: Age Cross-link Breaking and Inhibitory Activity Of S Aromatmentioning
confidence: 99%